(untitled) (Journal of the College of Education for Women, 2019)
NeighShrink is an efficient image denoising algorithm based on the discrete wavelettransform (DWT). Its disadvantage is to use a suboptimal universal threshold and identicalneighbouring window size in all wavelet subbands. Dengwen and Wengang proposed animproved method, which can determine an optimal threshold and neighbouring window sizefor every subband by the Stein’s unbiased risk estimate (SURE). Its denoising performance isconsiderably superior to NeighShrink and also outperforms SURE-LET, which is an up-todatedenoising algorithm based on the SURE. In this paper different wavelet transformfamilies are used with this improved method, the results show that Haar wavelet has thelowest performance among other wavelet functions. The system was implemented usingMATLAB R2010a. The average improvement in term of PSNR between Haar and otherwavelet functions is 1.37dB